C-geranylated flavanones from YingDe black tea and their antioxidant and α-glucosidase inhibition activities. (15th November 2017) - Zhou, Hua; Li, Hai-Mei; Du, Yang-Min; Yan, Ri-An; Ou, Shi-Yi; Chen, Tian-Feng; Wang, Yong; Zhou, Li-Xin; Fu, Liang
Highlights: Twelve phenolic compounds were isolated from YingDe Black tea for the first time. Amelliaones A and D were new C-geranylated flavanones. Five compounds showed α-glucosidase inhibitory and cytotoxic activities. Abstract: YingDe black tea is produced from crude tea prepared from leaves of Camellia sinensis var. assamica . In this work, we isolated and identified five novel flavanones, namely, amelliaoneA –E (1 –5 ), along with seven known compounds6 –12 from the ethanol extract of YingDe black tea. The structures of these five novel phenolic compounds were determined using extensive 1D and 2D nuclear magnetic resonance spectroscopy experiments. The compounds were further evaluated for antioxidant, α -glucosidase inhibitory, and cytotoxic activities. Compound1 exhibited higher α -glucosidase inhibitory activity with a half-maximum inhibitory concentration value (IC50 ) of 10.2 µM compared with acarbose (18.2 µM).